2018
DOI: 10.1002/jcb.27357
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Long noncoding RNA MALAT1 alleviates lipopolysaccharide‐induced inflammatory injury by upregulating microRNA‐19b in murine chondrogenic ATDC5 cells

Abstract: Osteoarthritis is the most frequent chronic bone-joint disease in middle-aged and older people worldwide. This study investigated the effects of long noncoding RNA metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) on lipopolysaccharide (LPS)-induced murine chondrogenic ATDC5 cell inflammatory injury. Cell viability and apoptosis were assessed using cell counting kit-8 assay and annexin V-phycoerythrin (PE) staining, respectively. The expression levels of interleukin-1β (IL)-1β, IL-6, IL-8, tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…First, ATDC5 cells were subjected to LPS to mimic an in vitro model of OA. In line with previous studies (Pan et al, ; Wang & Kong, ; Zhu et al, ), LPS induced a significant cell loss and pro‐inflammatory cytokines release, indicating ATDC5 cells were injured by LPS, and the cell model of OA was established successfully. Further experiments found that SIN treatment attenuated LPS‐induced cell injury, and the functional effects of SIN were implicated with the decreased expression of miR‐192 by SIN.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…First, ATDC5 cells were subjected to LPS to mimic an in vitro model of OA. In line with previous studies (Pan et al, ; Wang & Kong, ; Zhu et al, ), LPS induced a significant cell loss and pro‐inflammatory cytokines release, indicating ATDC5 cells were injured by LPS, and the cell model of OA was established successfully. Further experiments found that SIN treatment attenuated LPS‐induced cell injury, and the functional effects of SIN were implicated with the decreased expression of miR‐192 by SIN.…”
Section: Discussionsupporting
confidence: 86%
“…The objective of this study was to study the effects of SIN on mouse chondrogenic ATDC5 cells growth and inflammation and tried to reveal one of the possible underlying mechanisms. To this end, ATDC5 cells were subjected to lipopolysaccharide (LPS) to mimic an in vitro model of OA as previously described (Pan et al, ; Wang & Kong, ; Zhu, Wang, Teng, Chen, & Pan, ). Subsequently, ATDC5 cells were treated by SIN to see the effects of SIN on LPS injury to ATDC5 cells.…”
Section: Introductionmentioning
confidence: 99%
“…As Qiao et al [16] reported, miR-19b-3p alleviated LPS-induced inflammatory injury in human intestinal cells through regulating PI3K/AKT signaling pathways. Another study in osteoarthritis reported that miR-19b-3p was involved in the regulation of LPS-induced murine chondrogenic cell inflammatory injury by inactivating Wnt/β-catenin and NF-κB pathways [30]. It is known that the endothelium plays a crucial role in health and disease, and endothelial dysfunction has been determined to contribute to sepsis pathophysiology [3].…”
Section: Discussionmentioning
confidence: 99%
“…32 The same group explored the molecular action of KLF3-AS1 and found that it sponges miR-206 leading to the upregulation of G-protein-coupled receptor kinase interacting protein-1 and resulting in chondrocyte proliferation and apoptosis inhibition. 33 35 Osteoporosis is characterized by skeletal fragility and microarchitectural deterioration, 36 and differentiating bone marrow stromal cells to osteoblasts as a treatment has been an active area of research. 37,38 Zhang et al showed that osteogenic differentiation of bone marrow-derived MSCs was promoted by lncRNA NEAT1 via sponging miR29b-3p to upregulate BMP1.…”
Section: Musculoskeletal Systemmentioning
confidence: 99%